Identification, Classification and Zooarchaeology - Jonathan C. Driver (Ethnobiology Letters, 2011)
Identification of preserved biological materials is often regarded as a skill which has little to do with analysis and interpretation. This paper argues that in zooarchaeological studies―here with particular reference to vertebrate remains―identification procedures deserve more detailed consideration, because these procedures have a significant effect on the results of faunal studies. It is suggested that most identifications are made within a system of usually unspecified rules which vary from one analyst to another. Improvements in comparability between faunal studies will result if these rules are considered before beginning an analysis, and if the rules are made explicit in publications.